Impact of Infrapopliteal Angioplasty on Free Flap Survival in Diabetic Foot Ulcer Reconstruction - DUY QUANG THAI (The Graduate School, Ajou University, 2022)
Background The combination of revascularization followed by microvascular free flap transfer has been used for chronic ischemic wounds of the lower limb for several years. The purpose of this study was to determine the influence of angioplasty on free flap survival in diabetic foot ulcer reconstruction. Methods A retrospective research was conducted for 46 diabetic patients with chronic ulcers of the foot. All patients underwent free flap reconstruction due to their non-healing wound with tendon or bone exposure. Patients with severe peripheral arterial stenosis underwent angioplasty for increasing the distal perfusion before the flap surgery. Patient demographics, the data related to the vascular status, vascular intervention, and the free flap transfer procedure were collected. Flap survival rate was compared between the different groups of the severity of arterial stenosis, the revascularization results, and the recipient artery. Results The average age of patients was 56.2 ± 10.8 years. There 17 (37%) patients were smokers and 8 patients (17.4%) were with end-stage renal disease. Of 46 patients, 23 (50%) had severe infrapopliteal arterial stenosis. All of the patients with severe arterial stenosis underwent endovascular intervention. The post-procedural pedal arch was type 1 in 13 patients, type 2A in seven patients, type 2B in two patients, and type 3 in one patient. Total flap necrosis was found in 5 (10.9%) cases, marginal necrosis in 4 (8.7%) cases, and wound dehiscence in 4 (8.7%) cases. There was no significant difference in flap loss rate between severe arterial stenosis patients and non-severe arterial stenosis patients. In the severe arterial stenosis group, patients with type 1 of the post-procedural pedal arch had a significantly lower rate of total flap necrosis than the group of patients with type 2 and 3. There was no association between the use of revascularized recipient artery and flap survival. But ESRD is significantly associated with flap failure. Conclusions Our study revealed that the quality of the pedal arch was crucial for free flap survival. Thus, PTA should aim to re-establish a complete pedal arch to increase the wound healing rate and flap success.
학위논문(박사)--아주대학교 일반대학원 :의학과,2022. 2
Keywords: Angioplasty; Diabetic foot; Free flap; Peripheral arterial disease